Feasibility of salvage endoscopic resection for patients with locoregional failure after definitive radiotherapy for pharyngeal cancer - Satake, Hironaga; Yano, Tomonori; Yoda, Yusuke; Fujii, Satoshi; Zenda, Sadatomo; Tomioka, Toshifumi; Shinozaki, Takeshi; Miyazaki, Masakazu; Kaneko, Kazuhiro; Hayashi, Ryuichi (Endoscopy International Open, 2015)
Background and study aims: Local failure after radiation therapy for pharyngeal squamous cell carcinoma (PSCC) is problematic. The safety of endoscopic resection for lesions within the radiation therapy (RT) field has not been assessed. We evaluated salvage endoscopic resection in patients with locoregional failure after definitive radiotherapy for PSCC.Patients and methods: We retrospectively evaluated the clinical outcomes and long-term survival of 16 patients initially treated with more than 60 Gy of radiation for PSCC. These patients later presented with 19 superficial metachronous or recurrent PSCC lesions within the radiation field and were treated with salvage endoscopic resection. Results: Local recurrence developed at the primary site in 3 patients after a complete response to RT. The other 13 had multiple metachronous squamous cell carcinomas within the original RT field. Major complications associated with salvage endoscopic resection included aspiration pneumonia in 1 patient and a requirement for temporary tracheostomy in 3 patients. During a median follow-up period of 37 months (range, 2 – 72 months), 13 patients had no recurrence, 2 patients developed local recurrence, and 1 patient developed lymph node metastases. At present, 5 of the 16 patients have died: 2 of PSCC progression, 1 of esophageal squamous cell carcinoma, and the remaining 2 of unknown causes. The 3-year survival rate was 68.6 %.Conclusions: Endoscopic resection is a potentially curative salvage treatment option for patients with superficial locoregional failure after definitive radiotherapy for PSCC.